Internal surface pipe roughness classification : an acoustic emissions approach - Arif Johari, Mat Ali @ Salim (2009)
This project was carried out as a study of internal surface pipe roughness classification using single channel Acoustic Emissions (AE) technique. The objectives of this project are to detect Acoustic Emission (AE) signal from internal surface pipe and to classify smooth or rough of internal surface pipe using Acoustic Emission (AE). A test rig consists of the pipe with smooth internal surface and the pipe with rough internal surface using circumferential of a galvanized steel pipe used to run this experiment. Flow of water inside the pipe was controlled by a valve. The signal was captured using AE sensor with the help of Acoustic Emission Detector 2.1.3 software. For all pipe conditions, the values of hits, counts and RMS (average, maximum and minimum) were recorded and analyzed. All the values recorded were compared between the internal smooth pipe and internal rough pipe (90° and 360° opening valve). The results were gained from 10 marked points each for both pipe conditions. The result show that the different value of AE parameter between high flow rate (360° opening valve) and low flow rate (90° opening valve) for smooth pipe is greater than rough pipe. The total of RMS value was plotted for each flow rate and surface pipe roughness at each point. Based on Bangi number (AB) the value for rough pipe is 1.75 and below, meanwhile for smooth pipe is 1.75 and above. This value can be used for the classification of internal surface pipe roughness.